The suicidal patient clinical and legal standards of care - Bongar, Bruce Michael (American Psychological Association, 2013)
Suicide is uncomfortable to talk about, and many prefer to sweep the topic under the rug; but suicide remains a serious public health problem. This third edition of <xh:i>The Suicidal Patient</xh:i> by Bruce Bongar and Glenn Sullivan will prove to be an essential and vital resource for clinicians, supervisors, attorney, and clinicians in training"--Foreword. (PsycINFO Database Record (c) 2013 APA, all rights reserved)